Translating Breaches of Intersubjective Constraints on Interaction: the Case of Swearing in Roddy Doyle’s Novel The Commitments - Greenall, Annjo (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2011)
This article investigates the translation of breaches of Gricean maxims (and other constraints on interaction) in situations where the “same” maxim/constraint displays different normative strengths within two cultures. It is argued that if a breach of such constraints is transferred directly, the result will be a different degree of attention-getting effect and a possible change in the implicature in the target text. This point is illustrated by the analysis of the Norwegian translation of the Irish novel The Commitments. Here the translator perhaps unwittingly ignores the fact that the “swearing constraint” is stronger in Norwegian than in Irish English. Many of the breaches are transferred more or less directly, which means that the translation contains a number of potential shifts: the potential attention-getting effect is far stronger, and the (social) implicature is most likely skewed, at least for a generalized segment of the audience.